Computer programs that teach the interpretation of image-based laboratory tests. - Astion ML; LeCrone CN; Cookson BT; Orkand AR; Curtis JD; Wener MH; McGonagle LA; Fine JS; Pagliaro L (Clinical Laboratory Science)
OBJECTIVE: To review the effort of the University of Washington(UW) Department of Laboratory Medicine to develop and use personal computer programs to teach the interpretation of image-based clinical laboratory tests to medical technologists and other health care workers. DATA SOURCES: Professional journals and books; Software owned by and licensed by the University of Washington. STUDY SELECTION: Not applicable. DATA EXTRACTION: Not applicable. DATA SYNTHESIS: We have been developing interactive personal computer (PC) programs for teaching image-based laboratory tests to medical technologists and other health care workers. The programs, called 'Laboratory Tutors,' are useful for teaching microscope-based tests and tests based on electrophoresis. Our programs include ANA-Tutor, which teaches the immunofluorescence assay for anti-nucleat antibodies; GramStain-Tutor, which teaches the direct Gram stain; Electrophoresis-Tutor, which teaches the interpretation of agarose gel protein electrophoretic pattems, Urinalysis-Tutor, which teaches the microscopic examination of urine sediment; in addition to other programs. The tutorials are all based on high-quality digital images that were acquired and processed using digital imaging systems. They require minimal computer literacy and have a number of advantages over standard approaches to teaching image-based laboratory tests. The computer tutorials are used in UW's medical technology and medical school curriculum, where they are used as supplements to traditional instruction. CONCLUSION: Laboratory tutors are computer programs that use high resolution digital images to teach the interpretation of image-based laboratory tests. We plan to continue to develop these programs, study their educational effectiveness, and update them periodically.